'Makes head hurt': School-aged learners' perceptions in the language classroom. (August 2021) - Boye, Sarah; Gardiner, Ishamina Athirah; Littlejohn, Andrew
Abstract: This paper presents a research study which investigates the ways in which school-based language learners perceive the classroom. Concerned with the 'ecology' of the classroom, the aim of the study is to take language learners' own perceptions as a basis to understand more about the extent and types of learner engagement in the pedagogical dimension of the classroom. The study uses the repertory grid technique to collect data from lower-secondary language learners, and was chosen for the way it allows learners to speak for themselves. The data indicate that the school-based learners respond primarily with affect to classroom activities, and that behavioural, cognitive, and affective dimensions of learner engagement are not perceived as distinct categories by learners. The findings also show the development of a learner culture, where metacognitive strategies are used that allow learners to negotiate 'being taught' and serve purposes that diverge from the pedagogical purposes of the classroom as a space for language learning. The implications of these findings and possible teacher action in response to them are presented.